Mitos dalam Tegangan antara Figur Lelaki Ideal dan Realistis dalam Iklan Head & Shoulders “Joe Taslim x Fadil Jaidi” - Oktavia, Salsabilla Putri; Ramdani, Guruh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Visual elements play a strategic role in shaping consumer perceptions of advertisements, particularly within the context of contemporary digital communication. This study analyzes the representation of male figures in the Head & Shoulders advertisement titled